Dry sliding wear behaviour of Ti-TiB-TiNx in-situ composite synthesised by reactive hot pressing. (2016) - Silva, J.I.; Alves, A.C.; Pinto, A.M.; Silva, F.S.; Toptan, F.
Ti and its alloys are attractive materials for a variety of fields; however, a major problem of Ti and its alloys is their poor wear resistance. It is known that reinforcing Ti with hard ceramic phases can substantially improve the wear resistance. Thus, Ti-TiB-TiNx in-situ metal matrix composites were synthesised by reactive hot pressing utilising Ti/BN powder blends with 23:1 Ti:BN weight ratio. Ball-on-plate reciprocating dry sliding wear tests were performed against a 10 mm of alumina ball under 10 N normal load, at a frequency of 1 Hz, and with the total stroke length of 3 mm during 1, 800 s. Results showed that the total wear volume loss was significantly decreased on the composite (11.4 ± 2.0 × 10 −3 mm 3 ) as compared to the unreinforced Ti (40.9 ± 4.2 × 10 −3 mm 3 ) due to the strengthening effect of the in-situ reinforcing phases.